4 Psychoanalysis. - Arnold, Lucy (Year's Work in Critical & Cultural Theory, 2019)
In 2018 trauma emerged as one of the key preoccupations in the field of psychoanalytic scholarship, not only in terms of its manifestations in the clinic but in the social sphere and the cultural imaginary. This year's review examines six texts which, implicitly and explicitly, interrogate the significance and function of trauma from a range of standpoints. It is divided into four sections: 1. Introduction; 2. Theorizing Trauma and the Subject (which examines John L. Roberts's Trauma and the Ontology of the Modern Subject and Rudi Vermont's Reading Bion); 3. Memory, History, and Trauma (which explores Roger Frie's History Flows Through Us and Eric R. Severson and David M. Goodman's edited collection, Memories and Monsters: Psychology, Trauma and Narrative); 4. Mothers and (M)others—Trauma and the Family (which considers Jacqueline Rose's Mothers: An Essay on Love and Cruelty and Jean Owen and Naomi Segal's edited collection, On Replacement: Cultural, Social and Psychological Representations).